The called Alternative Law (Revista da Faculdade de Direito, Universidade de São Paulo, 1999)
Rule by judges from Rio Grande do Sul State: "The Law above the rule of law. The judge is bound to Justice not to the law. Unjust law must not be applied". Irrealistic ideal. In case of conflict in a concrete case the judge is asked not to follow his personal feeling of Justice, but to give a legal opinion concerning the law commandment on that concrete case. To avoid arbitrary opinion it is mandatory to avide by the law. A judicial decision in deliberate violation of the law justifies legal action against the judge. The true mission of the judge: to apply the law according to jurist's logic, that is, the logic of jurisprudence - the logic of the reasonable argument. The problem of interpretation of the legal rule. Justice and charity: the role of the these virtues on human activity.